Investigating teachers' job satisfaction, stress and working environment: The roles of self‐efficacy and school leadership - Jentsch, Armin; Hoferichter, Frances; Blömeke, Sigrid; König, Johannes; Kaiser, Gabriele (Psychology in the schools, 2023)
This study investigates the relations between working environment and teachers' job satisfaction, perceived work‐related stress, as well as work‐related self‐efficacy. The sample consisted of 226 mathematics teachers from German secondary schools. About 55% were female and they had been teaching for 13 years on average. We used self‐reported measures to assess how teachers perceived their working environment (regarding autonomy, feedback, and social support by colleagues), administrative leadership and teachers' work‐related self‐efficacy, as well as job satisfaction and work‐related stress. Structural equation modeling demonstrates that teachers' job satisfaction and stress were significantly associated with self‐efficacy (moderate to large effects) and an administrative leadership at the corresponding schools (small to moderate effects). The effect of social support on teachers' job satisfaction and stress was fully mediated by teachers' self‐efficacy. Our findings underscore the importance of self‐efficacy and a positive working environment for teachers' job satisfaction and stress. Practitioner Point Teachers' self‐efficacy is positively associated to their job satisfaction Frequent feedback by peers and efficient school leadership relate negatively to teachers' stress A supportive school environment could help teachers to increase their self‐efficacy